Agromorphological Characteristics of Cocoa from North Luwu Regency - Anggra Alfian; Marhani Marhani; Andi Besse Poleuleng (Agrologia, 2023)
North Luwu Regency is the leading cocoa-producing area in South Sulawesi. Cocoa development in North Luwu continues to be developed to increase production. One of the determining factors for the success of cocoa development, namely support for the availability of superior and quality planting materials. Therefore, it is necessary to continue developing and exploring clones in the field to obtain parents as cross material for developing new clones. This study aimed to determine the agro morphological characteristics of cocoa plants in several central villages in North Luwu Regency. The research was conducted in six cocoa-producing districts in North Luwu, namely Masamba, Baebunta, South Baebunta, Sabbang, Mappedeceng and Malangke, from July to November 2022. Observations were made using 27 agro morphological characters on 16 exposed cocoa clones. The results of the study showed high differences in character. These clones were grouped into two major groups, and the character of the fruit (fruit circumference) and seed (bean length) became the distinguishing characteristics of the cocoa clonesresulting from exploration in North Luwu.